Agar dilution susceptibility of Bacteroides spp. to sulfamethoxazole and trimethoprim: correlation with a disk diffusion technique. - Riley, T V (1981)
The minimum inhibitory concentrations of sulfamethoxazole and trimethoprim against 105 strains of Bacteroides spp. were determined by an agar dilution method, using Diagnostic Sensitivity Test agar supplemented with lysed blood. A total of 92% of the strains were susceptible to sulfamethoxazole alone (minimum inhibitory concentration, less than or equal to 50 microgram/ml), whereas only 28% were susceptible to trimethoprim alone (minimum inhibitory concentration, less than or equal to 1 microgram/ml). Susceptibility was also determined by a disk diffusion technique. For sulfamethoxazole, there was good correlation between inhibition zone diameters and minimum inhibitory concentrations. Hence, the disk diffusion test for susceptibility of Bacteroides spp. to sulfamethoxazole is suitable for routine laboratory testing. However, for trimethoprim there was a lack of correlation between the agar diffusion method and the minimum inhibitory concentrations. Three different methods for detecting synergy between sulfamethoxazole and trimethoprim against Bacteroides spp. were evaluated. With a checkerboard method, synergy was demonstrated in 96% of the strains which could be evaluated. However, this technique is unsuitable for routine testing. Two other techniques, which have been successfully used for detecting synergy with aerobic bacteria, were found to be unsatisfactory for Bacteroides spp.